Integrating the Qur’an and Science in Madurese Tafsīr: A Critical Examination of Muhammad Irsyad’s Interpretive Framework in Tapsèr Sorat Yaa-siin - Ramdhani, Fawaidur (Journal of Ushuluddin and Islamic Thought, 2024)
Scientific interpretation of the Qur’an in the Indonesian archipelago has shown significant development as part of academic discourse among Muslim scholars and intellectuals. This article critically examines Muhammad Irsyad’s interpretive framework in Tapsèr Sorat Yaa-siin (Bhāsa Madhurā), a Madurese commentary of the Qur’an that reflects integrative efforts between revelation and science. The existence of this work complements the variety of local interpetation with scientific nuances in Indonesia. Through a qualitative-descriptive approach based on literature review, this study maps Irsyad’s views on the relationship between the Qur’an and science using Campanini’s typology and analyzes his interpretative approach using Ian Barbour’s model. The findings reveal that the idea of integrating the Qur’an and science in Irsyad’s commentary is based on two main philosophical foundations. First, the Qur’an is not merely positioned as a sacred text conveying ritual-theological teachings but also contains a scientific dimension that encourages exploration of the universe. Second, Irsyad emphasizes that the Qur’an provides an ethical and methodological basis for understanding scientific phenomena. In its implementation, the integrative paradigm offered by Irsyad encompasses three essential concepts: (1) the integration of various branches of knowledge to explain phenomena comprehensively, (2) the Qur’an as the center of integration and the source of ethical values, and (3) tawḥīd as the ultimate goal and ontological foundation. Therefore, the interpretation of Tapsèr Sorat Yaa-siinnot only reflects a local response to modernity but also presents an epistemological model that harmoniously links revelation, reason, and scientific observation.